1997
DOI: 10.1002/eji.1830270145
|View full text |Cite
|
Sign up to set email alerts
|

Early B cell factor binds to a site critical for λ5 core enhancer activity

Abstract: The pre-B cell-specific expression of the lambda5 gene is regulated at the level of transcription. The 5' region of the lambda5 gene has been shown to contain an enhancer that activates heterologous promoters. Here, we show that this enhancer, B(lambda5), also acts as a lineage- and tissue-restricted enhancer on its own promoter. We define the enhancer core, b(lambda5), that carries around 50% of the total enhancer activity. We also demonstrate that the transcription factor early B cell factor (EBF) binds to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 32 publications
1
45
0
Order By: Relevance
“…The exact explanation for the B-cell phenotype observed in EBF-1-deficient mice is still unclear even though the protein has been suggested to be directly involved in the transcription regulation of several genes encoding components of the pre-Band B-cell receptor. These include the surrogate light-chain genes (41,50,53,57,58) and the B-cell receptor signal transducing molecules B29 (2), mb-1 (27,29) and Blk (3). The ability of EBF-1 to activate promoters controlling expression of the surrogate light chains appears to be conserved also in humans even though the primary DNA sequence of the promoters appears poorly preserved (24,25).…”
Section: O/e Proteins and B-lymphocyte Developmentmentioning
confidence: 99%
“…The exact explanation for the B-cell phenotype observed in EBF-1-deficient mice is still unclear even though the protein has been suggested to be directly involved in the transcription regulation of several genes encoding components of the pre-Band B-cell receptor. These include the surrogate light-chain genes (41,50,53,57,58) and the B-cell receptor signal transducing molecules B29 (2), mb-1 (27,29) and Blk (3). The ability of EBF-1 to activate promoters controlling expression of the surrogate light chains appears to be conserved also in humans even though the primary DNA sequence of the promoters appears poorly preserved (24,25).…”
Section: O/e Proteins and B-lymphocyte Developmentmentioning
confidence: 99%
“…Its gene product, together with VpreB1/VpreB2 and Ig heavy chain, forms the pre-B cell receptor (pre-BCR), which is crucial for normal B lymphocyte development and proliferation at the pre-B cell stage [2]. Expression of the murine Q 5 gene is regulated at the level of transcription, which is partly controlled by a region, 5' Q 5 , located immediately upstream of the coding sequence [3][4][5]. Detailed analyses in transient transfection assays have shown that the 722-bp 5' Q 5 fragment contains a promoter and an enhancer.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed analyses in transient transfection assays have shown that the 722-bp 5' Q 5 fragment contains a promoter and an enhancer. The promoter, A Q 5 , is active in all cell types, whereas the enhancer, B Q 5 , is active only in pre-B cells [3,5]. An˚100-bp enhancer core, b Q 5 , that carries approximately 50% of the activity of the full-length enhancer has also been defined [5], but its cell type preference has not been determined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One exemption is the promoter of the pre-B-cellspecific 5 gene (26,27), where E47 acts in synergy with EBF to stimulate transcription (58). This control element mediates stage-and lineage-specific expression of reporter genes both in transient transfections (32,33) and in transgenic mice (34). This makes the 5 promoter a useful model system to investigate B-cell-specific gene activation by bHLH proteins.…”
mentioning
confidence: 99%